Faktok-faktor yang Mendorong Wisatawan Menggunakan Transportasi Umum - Firdaus, Iqbal; Lesmini, Lis; Widiyanto, Prima (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
Bogor is popular for its tourist destinations among visitors. With the increasing number of domestic tourist arrivals, especially from the surrounding areas and Bogor itself, the availability of adequate public transportation is a must to support the tourism industry in the city. However, tourists prefer to use private vehicles for a visit that contributes to the increasingly severe traffic jams, especially in tourist destinations. This study aims to identify the preferences of tourist groups of public transport users and find out what factors drive them to use public transport in tourist areas. This study took place in Bogor Botanical Gardens and collected questionnaires from 401 respondents, meanwhile statistical analysis used was non-parametric chi-square test and confirmatory factor analysis. The result shows demographic factors affect the preferences of the use of public transportation, the difference in the level of satisfaction of tourists group of public transport users (regular users, infrequent users, and low users) to public transportation services in Bogor, and the similarity of main factors driving each group of tourists to use public transportation to do tourist activities in Bogor.